IMPLEMENTASI MANAJEMEN PESERTA DIDIK BERBASIS SEKOLAH DI TK ISLAM TERATAI PUTIH GLOBAL BEKASI - Ermawati, Eka; Murniarti, Erni; Sihotang, Hotmaulina (EDUPEDIA, 2023)
Student management is an arrangement and regulation of all activities related to students starting from the entry of students to the exit of these students from a school or educational institution. Student management activities are an important part that must be considered in the implementation of educational activities in schools. This aims to find out how student management plans, to find out how student learning is implemented, and to find out how learning evaluation is applied in the Lotus Putih Islamic Kindergarten Global School Bekasi. This study used qualitative research with a descriptive approach. Data collection was carried out using unstructured interviews/interviews and documentation. Sources of research data were obtained from school principals, vice principals, group A teachers, group B teachers, education staff, committees and guardians of students. The results of this study indicate that the Implementation of Student Management in the Teratai Putih Islamic Kindergarten Global School Bekasi has been well implemented. Student management aims to regulate student activities in learning and create a good school environment. It is concluded that student management indicators can analyze the needs of students starting from student acceptance to the orientation stage including discipline coaching and evaluation of learning outcomes at school